2006
DOI: 10.1038/nature04754
|View full text |Cite
|
Sign up to set email alerts
|

Transforming growth factor-β induces development of the TH17 lineage

Abstract: A new lineage of effector CD4+ T cells characterized by production of interleukin (IL)-17, the T-helper-17 (T(H)17) lineage, was recently described based on developmental and functional features distinct from those of classical T(H)1 and T(H)2 lineages. Like T(H)1 and T(H)2, T(H)17 cells almost certainly evolved to provide adaptive immunity tailored to specific classes of pathogens, such as extracellular bacteria. Aberrant T(H)17 responses have been implicated in a growing list of autoimmune disorders. T(H)17 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

96
2,275
10
34

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 2,802 publications
(2,430 citation statements)
references
References 26 publications
96
2,275
10
34
Order By: Relevance
“…In our study TGF-b was found to be spontaneously released, independent of any agonist. By detection of IL-1b, IL-6, IL-23, and TGF-b we found cytokines that recently have been proposed to be crucial for Th17 commitment [15][16][17][18][19]. However, even in human T cells, IL-23 seems to be responsible rather for enhancement than commitment of IL-17 [34], but in human CD8 1 T cells also IL-17 induction was observed [35].…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…In our study TGF-b was found to be spontaneously released, independent of any agonist. By detection of IL-1b, IL-6, IL-23, and TGF-b we found cytokines that recently have been proposed to be crucial for Th17 commitment [15][16][17][18][19]. However, even in human T cells, IL-23 seems to be responsible rather for enhancement than commitment of IL-17 [34], but in human CD8 1 T cells also IL-17 induction was observed [35].…”
Section: Discussionmentioning
confidence: 75%
“…A panel of cytokines have been proposed for induction of Th17 development. In mice, TGF-b together with IL-6 [15], with IL-23 [16], or with IL-6 and TNF-a [17] were reported to drive the Th17 cell fate. In humans, IL-1b and IL-6 [18] or IL-23 and IL-1b [19] were observed to be crucial for Th17 commitment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Th17 cells produce cytokines like IL-17, IL-22 and mediate immunity to extracellular bacteria and fungi, but are also responsible for autoimmunity and inflammation [12,13]. Development of naïve T cells to Th17 cells requires the presence of IL-6, TGF-b1 and the transcription factor RORgt [14][15][16][17]. [20,21].…”
mentioning
confidence: 99%
“…Previously, we had shown that Mina is required for normal in vitro differentiation of T helper 17 (Th17) cells 4, an inflammatory CD4 T helper subtype with host protective roles in fungal and certain mucosal bacterial infections as well as pathological roles in pulmonary inflammation and autoimmune diseases including multiple sclerosis and rheumatoid arthritis 14, 22. The development of Th17 cells can be driven in vitro by a combination of interleukin‐6 (IL6) and TGFβ 23. To explore whether E2 contributed to Mina transcription during in vitro differentiation of Th17 cells, we used deep sequencing to enumerate Mina mRNA molecules transcribed from each parental allele in developing Th17 cells generated from [BALB/c × C57BL/6]F1 (CB6F1) mice.…”
Section: Role Of E2 and Rs4191790 On Endogenous Mina Transcriptionmentioning
confidence: 99%